Menakar Inklusivitas Pertumbuhan Ekonomi di Provinsi Jambi: Analisis Pro-Poor Growth 2023–2024 - Angger Halim Ismail; Zulgani .; Cadra Mustika; Siti Hodijah; Nurhayani . (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to analyze changes in real poverty in Jambi Province between 2023 and 2024 using the Datt–Ravallion (1992) decomposition approach and Shapley decomposition through the DASP analysis package. The analysis was conducted separately for urban and rural areas to capture spatial differences in poverty dynamics. The data used came from the National Socioeconomic Survey (SUSENAS) with adjustments for inflation and the real poverty line, thereby reflecting actual changes in welfare rather than nominal changes.The results of the study show that the real poverty rate in urban areas of Jambi decreased from 10.19 percent in 2023 to 8.16 percent in 2024, while in rural areas it fell from 6.28 percent to 4.88 percent in the same period. However, Shapley decomposition shows that in both areas, the decline in poverty was due more to the effects of redistribution than to the effects of growth. In urban areas, the growth component (0.0031) actually slightly increased real poverty, while redistribution (–0.0234) contributed significantly to its decline. In rural areas, growth had only a small impact (0.0005), while redistribution (-0.0145) was the main factor in the decline in poverty. This shows that economic growth in Jambi Province is not yet fully inclusive (non-pro-poor growth), as the benefits of growth are still concentrated among the middle and upper classes, while improving income distribution is the key to reducing poverty. This study confirms that the effectiveness of poverty alleviation is determined not only by the rate of economic growth, but also by the quality and distribution of its results. The decomposition-based approach allows for more precise identification of the sources of poverty change and provides an empirical basis for the formulation of more inclusive and contextual development policies at the regional level.